Sex Is Associated With Differences in Individual Trajectories of Change in Social Health After Implantable Cardioverter-Defibrillator. (March 2015) - Lauck, Sandra B.; Sawatzky, Richard; Johnson, Joy L.; Humphries, Karin; Bennett, Matthew T.; Chakrabarti, Santabhanu; Kerr, Charles R.; Tung, Stanley; Yeung-Lai-Wah, John A.; Ratner, Pamela A.
Abstract : Background—: Social health is a dimension of quality of life, and refers to people's involvement in, and satisfaction with social roles, responsibilities, and activities. The implantable cardioverter-defibrillator is associated with changes in overall quality of life, but little is known about sex differences in individual trajectories of change in social health. Methods and Results—: We prospectively measured changes in 3 subscales of the SF-36v2 generic health questionnaire (role physical, role emotional, and social functioning), 2 Patient-Reported Outcomes Measurement Information System short forms (satisfaction with participation in social roles and satisfaction with participation in discretionary social activities), and the Florida Patient Acceptance Survey before and at 1, 2, and 6 months after implantation. Individual growth models of temporal change were estimated. The scores of the 6 indicators improved with time. The unconditional model demonstrated significant (fixed effects: P <0.05; covariance parameters: P <0.10) residual variability in the individual trajectories. In the conditional model, men and women differed significantly in their rates of change in the scores of 3 of the 6 measures. Although men's mean scores exceeded women's mean scores on all indicators at baseline (range of relative mean difference: 11.0% to 17.8%), the rate of women's change resulted in a reversal in relative standing at 6 months after implantation, with the mean scores of women exceeding the men's by 4.5% to 5.6%. Conclusions—: Men and women differed in their trajectories of change in social health, both in terms of their starting points (ie, baseline scores) and their rates of change. Abstract : Supplemental Digital Content is available in the text.